The Implementation of BrandCoVD™ in Local Online Transportation Brands: A Branderpreneurship Framing Analysis of Zendo - Manfaat, Jauhari; Ticoalu, Graceshiela Kezia Edelweis; Mochtar, Ditha Julia; Fariardhany, Fakhrureza; Pratikno, Ananto; Sari, Meri Indah (Jobmark: Journal of Branding and Marketing Communication, 2026)
Zendo is a startup brand born out of concern over the dominance of digital services in Indonesia, which tend to emphasize efficiency and profit, such as Grab and Gojek. Departing from the need for a more humanistic alternative, Zendo upholds the values of spirituality, empathy, and sustainability as its differentiator. This brand identity was built to provide digital services that are not only functional but also rich in social and emotional meaning. In this context, this study aims to examine how Zendo applies the BrandCoVD™ framework (Identifying, Creating, Delivering, Communicating, Maintaining, Evaluating, and Updating Values) in its branderpreneurship strategy. The study used the BFA (Branderpreneurship Framing Analysis) method, a qualitative-descriptive approach, and narrative analytical tools. Data were collected through in-depth interviews, one-on-one discussions, and focus groups. The analysis focused on each stage of BrandCoVD™ implementation as the foundation for brand identity development. The results show that Zendo successfully identified core values ​​through consumer research and brand narrative reflection. Value creation is achieved through service features and community programs that emphasize empathy and connectedness. The Zendo case study demonstrates that branderpreneur success is determined by the ability to build authentic meaning that is relevant and adaptable to changing times.